COMPLEX TREATMENT OF IRON DEFICIENCY ANEMIA WITH OBESITY IN WOMEN - Недоборенко, В.М. (World of Medicine and Biology, 2017)
The purpose of the study was to determine the effect of the inclusion of quercetin in the complex treatment of sick women in IDA with O for hematological parameters and QOL. 30 women were evaluated in a IDA with concomitant O that were distributed to the main group - 15 patients (n = 15) taking the basic treatment of iron sulfate with an additional oral administration of quercetin and a control group of 15 patients ( n = 15) who received baseline treatment. The comparison group consisted of 10 women (n = 10) of patients with IDA without O on baseline treatment. Evaluated hematological parameters and QOL by questionnaire SF-36. All patients were females with an average age of 40.3 ± 7.59 years. In the distribution of patients by the cause and the severity degree of IDA, there is no probable difference between the groups. In the course of treatment, a significant discrepancy of the indicators on the role of physical functioning (RFF) and viability (G) scales was noted for 60±3 days in the main group compared to the control group (p0,05). Conclusion. Incorporation of quercetin into a complex of treatment of iron deficiency anemia with obesity improves the physical component of quality of life quality on the scales of the RFF and G the SF-36 questionnaire in women with iron deficiency anemia with obesity.